A systematic computational analysis of the rRNA-3' UTR sequence complementarity suggests a regulatory mechanism influencing post-termination events in metazoan translation - Pánek, Josef; Kolář, Michal; Herrmannová, Anna; Valášek, Leoš Shivaya (RNA (New York, N.Y.), 2016)
Nucleic acid sequence complementarity underlies many fundamental biological processes. Although first noticed a long time ago, sequence complementarity between mRNAs and ribosomal RNAs still lacks a meaningful biological interpretation. Here we used statistical analysis of large-scale sequence data sets and high-throughput computing to explore complementarity between 18S and 28S rRNAs and mRNA 3' UTR sequences. By the analysis of 27,646 full-length 3' UTR sequences from 14 species covering both protozoans and metazoans, we show that the computed 18S rRNA complementarity creates an evolutionarily conserved localization pattern centered around the ribosomal mRNA entry channel, suggesting its biological relevance and functionality. Based on this specific pattern and earlier data showing that post-termination 80S ribosomes are not stably anchored at the stop codon and can migrate in both directions to codons that are cognate to the P-site deacylated tRNA, we propose that the 18S rRNA-mRNA complementarity selectively stabilizes post-termination ribosomal complexes to facilitate ribosome recycling. We thus demonstrate that the complementarity between 18S rRNA and 3' UTRs has a non-random nature and very likely carries information with a regulatory potential for translational control.
Keywords: Terminator Regions, Genetic; terminátorové oblasti (genetika); metazoan 18S rRNA–mRNA 3′ UTRs complementarity; 3' Untranslated Regions; 3' nepřekládaná oblast; zvířata; Codon; statistics; RNA ribozomální; RNA, Ribosomal; proteosyntéza; ribosomal recycling; translation termination; Protein Biosynthesis; large-scale data set; kodon; Animals